Humoral and Cellular Immune Regulation in Albino Rat Exposed to Glyphosate and Aluminum Phosphide - Ujuamala Ezeani; Onyemaechi Afonne; Michael Ezeani (Asia Pacific Journal of Medical Toxicology)
Background: Glyphosate (GLP) and Aluminum phosphide (ALP) pesticides remain vital for managing pests and disease vectors in both agriculture and public health. However, humans may experience chronic exposure to complex mixtures of pesticides from diverse environmental or dietary sources. The potential effects of this exposure on humoral and cellular immune processes are yet to be fully understood.Methods: The expression and potential regulation of T cells, specifically CD4+ helper T cells and CD8+ cytotoxic T lymphocytes, were evaluated in groups of male and female albino rats treated with oral distilled water; a low dose of glyphosate (1000 mg/kg/day); a high dose of glyphosate (3500 mg/kg/day); a low dose of ALP (1.1 mg/kg/day); and a high dose of ALP (5.0 mg/kg/day). This assessment was conducted using flow cytometry (Cyflow).Results: The results indicated that the pre-exposure stage exhibited a CD4+ to CD8+ ratio of 2:1. Subsequently, there was a significant increase in CD8+ values at the first, second and third months after exposure to GLP and ALP (p<0.001 for all). Additionally, there was a notable reduction in CD4+ levels at the second and third months post-exposure (p=0.001 and p<0.001, respectively).Conclusion: This study identified a deregulation of the immune system characterized by a progressive immunosuppression of CD4 T cell counts, indicating a down regulation of antibody-mediated (humoral) immune responses alongside an up regulation of cytotoxic T cells. This phenomenon aligns with the animals' increasing exposure to the chemicals, showing no significant difference in the changes due to dosage across both sexes. The chronic effects of these cytotoxic actions could potentially lead to tissue damage or trauma, resulting in subsequent chronic inflammation.